The effect of transformational leadership and work motivation on teacher performance in SMP Negeri 17 Cirebon City - Vina Andita Pratiwi; Endah Budiastuti; Sri Hartati; Nur Alia Sumanti; Yenni Rohmatun (Enrichment : Journal of Management, 2023)
This study was to determine the effect of transformational leadership style and work motivation on teacher performance at SMP Negeri 17 Kota Cirebon. The type of research used is a quantitative approach with multiple linear regression analysis techniques. The type of data used is primary data obtained through a questionnaire using SPSS for windows version 16. Secondary data is obtained from school data as well as several books and journals that can be accounted for. The sample in this study is 46 respondents which is the population of this study. The results of this study are that there is a significant influence between transformational leadership style and work motivation on teacher performance at SMP Negeri 17 Kota Cirebon. Based on the rules of the accepted hypothesis that the analysis test shows Tcount 3.931 > Ttable 2.017 with a significance value of 0.000 <0.050. There is no significant influence between work motivation on teacher performance at SMP Negeri 17 Kota Cirebon. Based on the accepted hypothesis, the analysis test shows Tcount 1.500 > Ttable 2.017 with a significance value of 0.141 > 0.050. There is a simultaneous significant effect of transformational leadership style and work motivation on teacher performance at SMP Negeri 17 Kota Cirebon. Based on the accepted hypothesis, this can be seen from the analysis Fcount 69.581 > Ftable 3.209 with a significance level of 0.000 <0.050. The research can have several expected implications, consist of improvement in teacher performance, enhanced educational outcomes, better school management and leadership training, motivation strategies, contribution to knowledge, policy formulation, and professional development.